Characterization and preparation of green colored intramolecular novel ball type cobalt phthalocyanine complexes with single-chain polymer structure - Abubakar, Abdullahi Musa; Demirelli, Kadir; Tuncer, Hulya; Salih, Bekir (Elsevier, 2021)
The single-chain polymeric-ball type CoPcs (SCP-ball type CoPcs) were synthesized via the intramolecular macrocyclization reaction of cobalt phthalocyanines from poly(PNDEAMSt2%-co-St) (as named precursor copolymerl) and poly(PNDEAMSt6%-co-St), as named precursor copolymer2) as precursors under diluted solution conditions at 155 degrees C in presence of cyclohexanol. SCP-ball type CoPc1 and SCP-ball type CoPc2 were prepared from precursor copolymerl and precursor copolymer2, respectively. The ball-type phthalocyanine moiety was incorporated into one side of the polymer chain. Both linear copolymer precursor and formation of ball-type cobalt phthalocyanine within a single-chain polymer were confirmed by FT-IR, H-1 NMR, UV/Vis spectroscopy and MALDI-TOF-MS techniques. Particularly, the formation of SCP-ball type CoPc2 complex was characterized by almost disappearance of -C = N band at 2230 cm(-1) of the FT-IR and appearance of Q band between 601 and 673 nm. Average apparent activation energies of the thermal degradation of SCP-ball type CoPc2 calculated by three model-free methods in a period of alpha=0.07-0.90 have been estimated, and the activation energy for weight loss from 7% to 90% was increased from 33.16kj/mol to 36.73kj/mol, respectively. Optical and dielectrical measurements of linear copolymer precursor2 and SCP-ball type CoPc2 were carried out. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Single chain polymer; Phthalocyanine; Characterization; Maldi-tof-ms